Tradeoff design of radio resource scheduling for power and spectrum utilizations in LTE uplink systems. (15th January 2017) - Kong, Cuiyu; Peng, I.-Hsuan
Abstract: Power and spectrum efficiency have been the concerns for the customers in Long term evolution (LTE) uplink system. On one hand, due to the limited spectrum, it is difficult to provide a high quality of service (QoS) to the user equipment (UE) in a heavy traffic load. On the other hand, people have been paying more attention to the energy efficiency because of the battery constraint and the decreasing size of the mobile devices. Even though the issues mentioned above have been addressed in the literature, the study about tradeoff design of both two issues is sparse. The rationale for the tradeoff is that due to the fast changeable channel conditions and unpredictable data requests from UEs, adopting the unique resource allocation scheme, either power-saving (PS) or spectrum-saving (SS) scheme, is not flexible. Therefore, this paper proposes a tradeoff method to dynamically choose either PS or SS scheme according to the changeable UE's request and channel conditions. In the proposed system, multi-class UEs are considered. The performance of the PS-only scheme, SS-only scheme and the proposed hybrid scheme (H-PSSS) are analyzed and compared. Results show that the proposed hybrid scheme achieves the desired performance.